The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/adfm.202108630
|View full text |Cite
|
Sign up to set email alerts
|

Combined Methylglyoxal Scavenger and Collagen Hydrogel Therapy Prevents Adverse Remodeling and Improves Cardiac Function Post‐Myocardial Infarction

Abstract: Methylglyoxal (MG) is a highly reactive dicarbonyl and the main precursor of advanced glycation end-products (AGEs). After myocardial infarction (MI), MG-derivedAGEs accumulate in the heart and contribute to adverse remodeling and loss of cardiac function. In this study, the flavonoid fisetin, a dicarbonyl scavenger, is used to reduce the negative effects of MG in the post-MI heart. A fisetin-loaded collagen type I hydrogel (fisetin-HG) is injected intramyocardially in mice at 3 h post-MI, and compared to fise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…The lower levels of MG‐H1 found throughout the myocardium on day 2, both on collagen and within cardiomyocytes, result in a reduction in oxidative stress, leading to less cardiomyocyte death and greater myocardial salvage at 28 days. Recently, we reported that a combined dicarbonyl scavenger (fisetin) and collagen hydrogel therapy delivered at 3 h post‐MI was able to prevent adverse remodeling and improve cardiac function by reducing the accumulation and negative effects of MG. [ 57 ] While the combined fisetin‐hydrogel treatment was the most effective, the hydrogel‐only control treatment also reduced MG‐AGE levels and oxidative stress leading to less cell death and improved cardiac function. This suggests a novel mechanism by which the hydrogel confers its therapeutic benefit; it acts as a sponge to remove toxic MG from the post‐MI environment leading to enhanced repair and functional restoration.…”
Section: Discussionmentioning
confidence: 99%
“…The lower levels of MG‐H1 found throughout the myocardium on day 2, both on collagen and within cardiomyocytes, result in a reduction in oxidative stress, leading to less cardiomyocyte death and greater myocardial salvage at 28 days. Recently, we reported that a combined dicarbonyl scavenger (fisetin) and collagen hydrogel therapy delivered at 3 h post‐MI was able to prevent adverse remodeling and improve cardiac function by reducing the accumulation and negative effects of MG. [ 57 ] While the combined fisetin‐hydrogel treatment was the most effective, the hydrogel‐only control treatment also reduced MG‐AGE levels and oxidative stress leading to less cell death and improved cardiac function. This suggests a novel mechanism by which the hydrogel confers its therapeutic benefit; it acts as a sponge to remove toxic MG from the post‐MI environment leading to enhanced repair and functional restoration.…”
Section: Discussionmentioning
confidence: 99%
“…Used for hiPSC cultivation and as a proper microenvironment for cell grafts, SpGel could induce hiPSCs into ECs and cardiomyocytes with an enhanced function against the ischemic environment . Within a thermoresponsive collagen hydrogel, fisetin was administered directly to the myocardium for treating MI minimized inflammation and promoted vascularization, finally improving cardiac function of the mouse heart post-MI …”
Section: Hydrogels With Heart-specific Mimicry and Functionalitymentioning
confidence: 99%
“…114 Within a thermoresponsive collagen hydrogel, fisetin was administered directly to the myocardium for treating MI minimized inflammation and promoted vascularization, finally improving cardiac function of the mouse heart post-MI. 115 Nanofibrous gelling microspheres (NF-GMS) assembled by poly(L-lactic acid)-b-poly(ethylene glycol)-b-poly(N-isopropylacrylamide) possessed a thermal-responsive transition for 3Dgeometry hydrogel formation, and ECM-mimicking features integrated with nanofibrous, proteins, gelling proteoglycans and polysaccharides. 116 Another thermosensitive chitosanvitamin C (CSVC) hydrogel scaffold conjugated by Vitamin C was found with stronger antioxidant and injectable properties, a suitable gelation time and a higher solubility to reduce oxidative stress post-MI injury.…”
Section: Conductivitymentioning
confidence: 99%
“…Upon the combination of hydrogel with functional factor/protein, drug, and gene for myocardial infarction treatment, it mainly plays a role in local delivery and controllable release. Injectable hydrogel forms a stable solid scaffold in the infarct area after coagulation, and the wrapped factor/protein, drug, and gene are continuously released to avoid their rapid metabolism [ 140 , 141 , 142 ]. Injectable hydrogel systems can out-performance traditional drug delivery methods, due to their advantages such as low invasiveness, high efficiency, and sustained local delivery [ 41 , 50 ].…”
Section: Hydrogels As Factor/protein Drug Gene Release Carriersmentioning
confidence: 99%